ANALYSIS OF UKRAINE’S TRANSITION TO STIMULATING TARIFFS - Savelyev, Yevhen; Kuryliak, Vitalina; Lyzun, Maria; Lishchynskyi, Ihor (Journal of European Economy, 2018)
The prerequisites of public transport electrification and the need to reduce CO2 emissions in the transport sector are investigated. It has been established that electricity is a universal energy source that can help diversify primary energy sources for transport and increase energy security. Positive socio-economic effects from the use of electricity in the transport sector are identified. The competitive advantages of using electric transport in the system of public transportation are determined. Global experience of electrification of passenger transportation is analyzed. An important driving force for the creation and development of the market was government support, which was carried out by adopting relevant legislative norms and implementing various initiatives at both the national and regional levels. The development of the legislative framework for the support of environmentally friendly modes of transport in the world economy markets is divided into stages. The current state of public electric transport in Ukraine is explored. The system of reform measures for the public electric transport in Ukraine is determined. JEL: R41, R42, R49.